Commercial Real Estate and Financial Stability : Evidence from the US Banking Sector - Fendoglu, Salih (International Monetary Fund, 2021)
This note analyzes the implications of changes in commercial real estate (CRE) prices for the stability of the US banking sector. Using detailed bank-level and CRE price data for US metropolitan statistical areas, the analysis shows that, following a decline in CRE prices, banks with greater exposures to CRE loans perform worse than their counterparts, experiencing higher non-performing CRE loans, lower revenues, and lower capital. These effects are particularly pronounced if the drop in CRE prices turns out to be persistent because of possible structural shifts in CRE demand-for example, because of an increased trend toward e-commerce and teleworking-even after the coronavirus disease (COVID-19) pandemic is over. The impact of a decline in CRE prices is especially true for small and community banks, which tend to have the highest CRE loan exposures. While the US banking sector has remained resilient during the pandemic crisis due to strong capital buffers and massive policy support, these findings suggest that continued vigilance is warranted with regard to potential downside risks to CRE prices amidst ongoing structural shifts in the sector.